2017
DOI: 10.1021/acsami.7b11446
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed Plasmonic–Dielectric Sunlight-Collecting Nanofilms for Solar Thermoelectric Application

Abstract: It is important but remains a challenge to develop solution-processed plasmonic solar thermoelectricity films on various substrates, without strictly considering hierarchical plasmonic-dielectric-metal structures, to harvest a wide range of visible to near-infrared sunlight. We simply fabricate plasmonic silica metastructure sunlight-collecting nanofilms on highly reflective Cu and Si surfaces by introducing spin coating (with an Ag and silica colloidal mixture, a spin coater, and a heating plate) and low-temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…[17,18] Since the electric potential difference (∆V) generated from a TE device is proportional to the temperature difference across the device (∆T) and the Seebeck coefficient (S), as expressed by ΔV = SΔT, 17,18 plasmonic NPs have been coated on the top surface of a TE module to generate heat upon solar illumination. [19][20][21][22][23] In this approach, the amount of absorbed solar radiation and the heat produced by plasmonic NPs are largely determined by the overlap between the spectrum of solar radiation and the extinction of the NPs. However, many plasmonic NPs have narrow extinction in the visible light region, particularly for spherical Ag and Au NPs, resulting in limited spectral overlap.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] Since the electric potential difference (∆V) generated from a TE device is proportional to the temperature difference across the device (∆T) and the Seebeck coefficient (S), as expressed by ΔV = SΔT, 17,18 plasmonic NPs have been coated on the top surface of a TE module to generate heat upon solar illumination. [19][20][21][22][23] In this approach, the amount of absorbed solar radiation and the heat produced by plasmonic NPs are largely determined by the overlap between the spectrum of solar radiation and the extinction of the NPs. However, many plasmonic NPs have narrow extinction in the visible light region, particularly for spherical Ag and Au NPs, resulting in limited spectral overlap.…”
Section: Introductionmentioning
confidence: 99%
“…Another key component in our design lies in the integration of a foam (low thermal conductivity, about 35 mW m –1 K –1 ) around the thermoelectric device to provide an insulating air layer for efficient heat localization while minimizing fluctuations arising from environmental factors. Consequently, our solar–thermal generator achieves stable and effective solar–thermal–electric conversion with a V OC , I SC , and maximal power output of around 0.3 V, 30 mA, and 3.3 mW, respectively, under 1 sun at room temperature (loading resistance, 13 Ω), notably superior over other reported designs. ,, Furthermore, our design also enables stable and effective power generation across wide ranges of ambient temperatures (0–25 °C) and solar intensities (1–7 suns). When coupled with a transformation module, a series of multiple solar-driven generators can efficiently charge the mobile phone under sunlight irradiation, attaining an increase in mobile phone power at a rate of 5% per hour.…”
Section: Introductionmentioning
confidence: 89%
“…[27] The top side of the ribbon device is the PDRC layer and the bottom side is the SSA layer to realize a large temperature gradient for electricity output. Unlike other 3D STE devices, [2,11,28] our SSA parts are always in the bottom, ensuring that the waste heat and solar energy can be utilized simultaneously. Figure 1b displays the fabrication procedure of the helical ribbons.…”
Section: Design and Manufacture Of Ste Devicesmentioning
confidence: 99%
“…[ 2,4,7 ] For example, Suarez et al reported that an STE device provided a low thermal conductivity filler (air) paralleling the TE legs to optimize the thermal impedance. [ 6 ] On the other hand, although diverse strategies were successively employed to settle down the thermal dissipation of the cold side, including heat sink, [ 8,9 ] appropriate air velocities, [ 10 ] and circulation water, [ 11,12 ] these methods use rigid and bulky instruments, even leading to dissipate more energy, which increases the cost of large‐scale application. Other reported studies cooled the cold side by the latent heat of water evaporation of hydrogel.…”
Section: Introductionmentioning
confidence: 99%